2014
DOI: 10.1111/jeu.12149
|View full text |Cite
|
Sign up to set email alerts
|

Twenty Years of Acanthamoeba Diagnostics in Austria

Abstract: Acanthamoebae are the causative agents of an often seriously progressing keratitis (AK) occurring predominantly in contact lens wearers and can cause several disseminating infections potentially resulting in granulomatous amoebic encephalitis (GAE) in the immunocompromised host. Our institution is the Austrian reference laboratory for Acanthamoeba diagnostics and the aim of this study was to give an overview of proven cases of Acanthamoeba infections in Austria during the past 20 yr. All samples of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 60 publications
4
67
0
8
Order By: Relevance
“…isolate of genotype T6 was also found associated with Acanthamoeba keratitis in 2012 (Blaschitz et al, 2006). In a 20 year study by Walochnik et al (2015) it was reported that, apart from the predominant genotype T4, several other genotypes, such as T3, T4, T5, T6, T10 and T11, were associated with Acanthamoeba keratitis . Genotype T15, mostly reported from environmental sources, was found as a causative agent of protracted keratitis in humans (Sharifi et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…isolate of genotype T6 was also found associated with Acanthamoeba keratitis in 2012 (Blaschitz et al, 2006). In a 20 year study by Walochnik et al (2015) it was reported that, apart from the predominant genotype T4, several other genotypes, such as T3, T4, T5, T6, T10 and T11, were associated with Acanthamoeba keratitis . Genotype T15, mostly reported from environmental sources, was found as a causative agent of protracted keratitis in humans (Sharifi et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Typically, amebas inhabit the lens case via tap water, rapidly multiply if the case is not cleaned properly and regularly, and then infect the eye via the CLs. 36 …”
Section: Risk Factorsmentioning
confidence: 99%
“…E n u n e s t u d i o r e a l i z a d o p o r Wa l o c h n i k y colaboradores, se observó que en las muestras de pacientes que recibieron tratamiento antimicótico o antibiótico tardaban más en detectar el parásito y en algunos casos los cultivos permanecieron negativos por completo, mientras que al realizar un seguimiento del paciente a medida que avanzaba con el tratamiento observaron una variada sensibilidad respecto a las muestras iniciales de 85% (primera muestra) a 10% (muestras de seguimiento) por el método de cultivo, lo que sugiere la necesidad de contar con métodos más sensibles y específicos para asegurar la detección del (35) parásito .…”
Section: Métodos De Diagnósticounclassified
“…La dificultad para eliminar completamente el parásito se debe a los quistes altamente resistentes. Otro estudio realizado por Antonelli y colaboradores reportó el caso de un paciente que seguía dando positivo por cultivo y PCR tras ser sometido a 8 meses de terapia continua, lo que demuestra la alta persistencia y resistencia de (24,35,38) Acanthamoeba .…”
Section: Métodos De Diagnósticounclassified